An extremely rare disconnection of the external iliac artery and novel collateral remodeling in an endometrial stromal sarcoma woman - Shixuan Wang; Ting Zhou; Nan Yu; Ronghua Liu (BMC Women's Health, 2022)
Abstract Background Injury to the external iliac artery can have serious consequences and can be extremely challenging for surgeons. Here, we report a patient with bizarre disconnection of the external iliac artery during a laparoscopic operation. Case presentation On May 27, 2020, during a laparoscopic pelvic lymphadenectomy operation to treat endometrial stromal sarcoma, we encountered an unusual anatomy: abnormal disconnection of the left external iliac artery in a 26-year-old female patient. The proximal and distal ends of the left external iliac artery demonstrated old narrowing without active bleeding, and the distance between the two disconnected ends was more than 3 cm. The scenario was surprising to all the staff in the operating theater. After a comprehensive assessment of skin temperature, arterial pulsation and arterial blood flow, a multidisciplinary team determined that collateral circulation of the left lower limb had been established and could meet the blood supply of the lower limbs, which was also confirmed three times by computed tomography angiography and Doppler ultrasound of the blood vessels in the abdomen and lower limbs. Sixteen months after the operation, the patient had no obvious abnormality, and the daily activities of the left lower limb were not affected. Follow-up after treatment for the patient is still in progress. Conclusions We describe the details of the whole case of disconnection of the external iliac artery. We hope to summarize the experience and lessons learned through this case and a relevant literature review to improve the safety and orderliness of our future clinical work.